Impact of Iodinated Contrast Media in Patients Received Percutaneous Coronary Intervention: Focus on Thyroid Disease - Chen, Yasha; Zheng, Xueyang; Li, Na; Niu, Wenhao; Hu, Bowen; Yuan, Xun; Liang, Chun; Lin, Yunling (Frontiers in Endocrinology, 2022)
Background: With the rapid advance in percutaneous coronary intervention (PCI) technology, patients absorb large volume of iodinated contrast media (ICM). The association between ICM volume and thyroid is still unclear. We sought to evaluate the long-term influence of ICM on thyroid dysfunction and disease in patients received PCI. Methods: This single-center retrospective study included consecutive coronary artery disease (CAD) patients. A covariance (ANCOVA) model was performed to evaluate the change of serum TSH, FT3 and FT4 before and one-year after the PCI procedure. Restricted quadratic splines and logistic regression were performed to evaluate the association between ICM volume and thyroid disease. Results: 2062 patients met inclusion criteria (1381 patients in the low-volume group and 681 patients in the high-volume group). The serum TSH of the high-volume group was 0.154 ± 0.078 MIU/L lower (P = 0.048), and the serum FT4 was 0.238 ± 0.092 pmol/L higher than the low-volume group (P = 0.010). Restricted cubic splines show that there were linear dose-response relationships for ICM volume and composite endpoint and hyperthyroidism. In all models, there were significant differences in composite endpoint between the two groups. (OR 1.75, 95% CI (1.05, 2.92), P = 0.032, OR 1.73, 95% CI (1.01-2.96), P = 0.032 and OR 1.83, 95% CI (1.09-3.06), P = 0.022, respectively). The positive results were also showed for hyperthyroidism in all models (OR 2.35, 95% CI (1.14-4.84), P = 0.021, OR 10.36, 95% CI (1.20-89.00), P = 0.033 and OR 2.35, 95% CI (1.13-4.87), P = 0.022, respectively). Conclusion: The present analysis gives an overview that ICM volume is associated with an increased risk of thyroid dysfunction and thyroid disease.